Micro and small enterprise upgrading in the Philippines: the role of the entrepreneur, enterprise, networks and business environment - Aimée Hampel-Milagrosa (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
In developing countries, micro and small enterprises (MSEs) comprise the largest part of the industrial fabric – offering millions of people worldwide the chance to be employed and earn livelihoods. However, empirical evidence suggests that a large majority of MSEs never manage to upgrade significantly. Defining upgrading as “growth through innovation” and using the Philippines as a country case, this study evaluates the constraints and success factors for Filipino-owned MSEs to upgrade. It finds that the entrepreneurs' characteristics and strategies for coping with a range of structural and sectoral constraints are the most important factors for success: entrepreneurs singlehandedly upgrade their firms by ingeniously substituting or complementing factors of production. However, such super entrepreneurs are born into lives of privilege and opportunity. For this reason, now more than ever, creating a level playing field for all should be a priority for both policymakers and donors.
Keywords: 330; Strukturwandel; wirtschaftliche Entwicklung und Beschäftigung